2003
DOI: 10.1373/49.3.487
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Lactate and Pyruvate Concentrations and Their Ratio in Children: Age-related Reference Intervals

Abstract: Background: Lactate (L) and pyruvate (P) concentrations in cerebrospinal fluid (CSF) and the L/P ratio have diagnostic value in numerous primary and acquired disorders affecting the central nervous system, but agerelated reference values are not available for children. Methods: We analyzed CSF and blood lactate and pyruvate concentrations and their ratio in a 4-year retrospective survey of a children's hospital laboratory database. Reference intervals (10th-90th percentiles) were established from data on 197 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 18 publications
3
23
0
4
Order By: Relevance
“…We found a clear age-dependent pattern for CSF lactate. A slight variation with age of the CSF lactate has been described before in a study of children aged 0–15 years [26], with 95 th percentile values around 1.95 mmol/L. Higher 95 th percentiles for children under the age of 6 months were found in the present study (2.01–2.64 mmol/L).…”
Section: Discussionsupporting
confidence: 80%
“…We found a clear age-dependent pattern for CSF lactate. A slight variation with age of the CSF lactate has been described before in a study of children aged 0–15 years [26], with 95 th percentile values around 1.95 mmol/L. Higher 95 th percentiles for children under the age of 6 months were found in the present study (2.01–2.64 mmol/L).…”
Section: Discussionsupporting
confidence: 80%
“…The CSF lactate reference interval of 1.0-2.2 mmol/L derived in this study is comparable to that observed in previous reports [11][12][13][14] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 More work is required to accurately determine the degree of age-dependent bias on larger data sets in which relevant pathology has been excluded.…”
Section: Discussionsupporting
confidence: 90%
“…In human beings, some studies support that CSF pyruvate decreases and lactate and L/P ratio increase with age (Benoist and others 2003, Wilhelmina and others 2012). However, in one recent study, a positive correlation has been described between the CSF pyruvate concentration and age (Zhang and Natowicz 2012).…”
mentioning
confidence: 98%
“…Alterations in CSF levels of different neurotransmitters, enzymes and neuronal metabolic substrates have been found in different diseases affecting the CNS in dogs and cats (Di Terlizzi and Platt 2006). CSF lactate, pyruvate and lactate/pyruvate ratio (L/P ratio) have been proposed as biomarkers of brain energy metabolism (BEM) in humans (Parnetti and others 2000, Benoist and others 2003, Djukic and others 2012) and dogs (Sugi and others 1975, Pugliese and others 2005). Changes in concentration of these metabolites have been observed when oxidative damage, brain hypoxia or mitochondrial damage is present (Sugi and others 1975, Benoist and others 2003, Pugliese and others 2005).…”
mentioning
confidence: 99%